Efeito das superfícies nano e micro estruturadas sobre a ebulição nucleada - Kiyomura, Igor Seicho [UNESP] (2016)
In the last decade, the necessity to dissipate large quantities of heat energy increased, thus leading to an increase on the number of studies in nucleate pool boiling and flow boiling with the aim of producing more compact and efficient heat exchangers. The search for increasingly efficient and compact products and for new techniques to improve the heat transfer, ensuring the physical integrity of the equipment, keep growing and it will remain so in the next years. One of the techniques being widely researched in the scientific community is the use of nanofluids. The nanofluids have been developed in order to improve the thermal conductivity and diffusivity compared to traditional fluids. Although many experiments with nanofluids have been developed in recent years, there are still many differences related to the effects of these fluids on the pool boiling phenomenon. In this context, this work aims to analyze the effects of nanostructured surfaces and different nanofluid concentrations, which are deposited on the heating surface, on the heat transfer coefficient during the nucleate boiling regime. Therefore, tests were performed to heat fluxes values corresponding to the nucleate boiling regime for deionized water, at saturation temperature (Tsat = 99 °C) and atmospheric pressure (patm = 98 kPa), on copper heating surfaces with different roughness values. The nanostructured surfaces were produced by maghemite nanoparticle deposition, which is achieved by boiling selected mass concentrations of a Fe2O3-deionized water nanofluid. Prior and after each boiling test, the characteristics of the test surfaces were evaluated by applying the metallographic, wettability and surface roughness tests. The results for the heat transfer coefficient were related to the geometrical and morphological characteristics of the test surfaces, taking into account the aspects of the flu-id/surface interaction such as, the contact angle and wettability.